R-T-B sintered neodymium-iron-boron magnet and preparation method thereof

By designing and combining elements of the sintered NdFeB magnet matrix, the diffusion effect of heavy rare earth elements along the grain boundary is improved, and the composite phase is formed to improve the wettability of grain boundary, which solves the shortcomings in the comprehensive performance of existing magnets and achieves higher magnetic properties.

CN119673652APending Publication Date: 2025-03-21JL MAG RARE EARTH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411912784.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing sintered NdFeB magnets still need to be improved in their overall performance and cannot meet the high performance requirements in downstream application fields.

Method used

By rationally designing and combining rare earth elements, non-rare earth elements and diffusion alloy elements of the magnet matrix, the effect of heavy rare earth elements diffusing along the grain boundary is improved, and a composite phase is formed to improve grain boundary wetting and magnetic properties.

Benefits of technology

It effectively improves magnetic performance, especially coercive force, residual magnetism and magnetic energy product, and meets the high performance requirements of downstream applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005206145620000111
    Figure BDA0005206145620000111
  • Figure BDA0005206145620000112
    Figure BDA0005206145620000112
  • Figure BDA0005206145620000121
    Figure BDA0005206145620000121
Patent Text Reader

Abstract

The invention provides an R-T-B sintered neodymium-iron-boron magnet and a preparation method thereof. Alloy elements and rare earth elements are reasonably designed, meanwhile, in the sintering and aging process, a composite phase is formed, the wettability of a grain boundary can be improved, heavy rare earth elements can enter the deep position of the magnet along the grain boundary in the subsequent diffusion process, and by forming a specific component proportion with a diffusion source, the rare earth elements can be effectively prevented from entering the deep position of the magnet. The diffusion effect of heavy rare earth elements along the grain boundary is improved, and the magnetic performance can be further improved. Ti / Zr / Nb elements are added, the adding amount is increased, and the intrinsic coercive force of the magnet alloy is improved by controlling the fixed proportion of Ti and Cu elements and utilizing the grain refinement effect of a TiCu composite phase; and meanwhile, copper-titanium moves relative to the grain boundary of magnetic phase grains to generate a pinning effect, so that the sintering-resistant temperature is improved, abnormal growth of the grains is avoided, the change of the magnetic phase can be prevented, the grains are refined, and then the residual magnetism, coercive force and magnetic energy product of the magnet alloy are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of NdFeB magnet materials and relates to an RTB sintered NdFeB magnet and a preparation method thereof. Background Art

[0002] Sintered NdFeB is the permanent magnet with the highest energy density discovered by mankind so far, and has now achieved large-scale commercial production. Since its discovery, sintered NdFeB sintered magnets have gradually been used in many aspects, and their application range and output are increasing year by year. As a functional material with important influence, it has been widely used in energy, transportation, communication, machinery, medical treatment, computers, home appliances, and national defense science and technology, and has penetrated into all aspects of national economy and people's livelihood.

[0003] As the demand for the performance of sintered NdFeB magnets in downstream applications continues to increase, the industry is constantly conducting research on it. Grain boundary diffusion technology is a method of improving material properties by introducing diffusion elements at the grain boundaries of the material. This method can increase the coercivity of the magnet while maintaining a high remanence and magnetic energy product. For example, using Dy and Tb to partially replace Nd to increase the coercivity of NdFeB sintered magnets through grain boundary diffusion is also a common method in the industry.

[0004] However, due to the increasing requirements of subsequent applications, the current method of using diffusion alloys to improve the performance of sintered NdFeB magnets needs to be further improved in terms of its comprehensive performance.

[0005] Therefore, how to find a more suitable way to solve the above problems existing in the current sintered NdFeB magnets has become one of the problems that many manufacturers and researchers in the industry need to solve urgently. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a RTB sintered NdFeB magnet and a preparation method thereof. The present invention improves the effect of diffusion of heavy rare earth elements along grain boundaries by rationally designing and combining rare earth elements, non-rare earth elements and diffusion alloy elements of the magnet matrix, which can further improve the magnetic properties.

[0007] The present invention provides a RTB sintered NdFeB magnet, comprising: a sintered NdFeB substrate and a diffusion alloy composited on the substrate;

[0008] The general formula of the substrate by mass content is R1 x T 余量 M y1 A y2 B z; Wherein, R1 is selected from at least two rare earth elements and must include Pr and Nd; A is selected from Cu, Ga and Al; M is selected from one or more of Ti, Zr and Nb, and must include Ti; T is selected from Fe and Co;

[0009] In the general formula of the substrate, 28.5wt%≤x≤32.0wt%, 0.13wt%≤y1≤0.5wt%, 0.2wt%≤y2≤1.35wt%, 0.8wt%≤z≤1.2wt%;

[0010] The general formula of the diffusion alloy by mass content is R2 a N b ; Wherein, R2 is selected from one or more heavy rare earth elements; N includes one or more of Al, Cu, Zn, Sn and Ga;

[0011] In the general formula of the diffusion alloy, 80wt%≤a≤100wt%, b≤20wt%;

[0012] The diffusion alloy accounts for 0.2wt% to 1.5wt% of the total amount of the RTB sintered NdFeB magnet;

[0013] The components of the RTB sintered NdFeB magnet have the following mass content relationship:

[0014] 3(y1+y2)-[R2 a N b ]>0.5wt%.

[0015] Preferably, in the M, 0.3wt%>Ti+Zr / 2+Nb / 3≥0.13wt%, Ti>0, Zr≥0, Nb≥0;

[0016] In the A, 0.8wt%>Cu>0.18wt%, the content of Ga is 0.25wt%-0.45wt%, and the content of Al is 0.02-0.5wt%.

[0017] Preferably, in the RTB sintered NdFeB magnet, the Ti-based precipitated phase is a Ti-Cu phase;

[0018] In the RTB sintered NdFeB magnet, the mass content ratio of Ti to Cu is (1-3):5.

[0019] Preferably, the substrate accounts for 98.8wt% to 99.7wt% of the total amount of the RTB sintered NdFeB magnet;

[0020] The diffusion alloy accounts for 0.3wt% to 1.2wt% of the total amount of the RTB sintered NdFeB magnet.

[0021] Preferably, in the T, the content of Co is 0.01wt% to 1.0wt%, and the balance is Fe;

[0022] The heavy rare earth element includes one or more of Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu and Y;

[0023] The RTB sintered NdFeB magnet has an average grain size of 2.5 to 6 μm after sintering.

[0024] The present invention provides a method for preparing an RTB sintered NdFeB magnet as described in any one of the above technical solutions, comprising the following steps:

[0025] A) the raw materials are mixed according to the proportion and then subjected to quick-setting thin sheet treatment to obtain NdFeB quick-setting thin sheets;

[0026] B) subjecting the NdFeB quick-solidification flakes obtained in the above steps to hydrogen crushing and jet milling in sequence to obtain NdFeB powder;

[0027] C) orienting and molding the NdFeB powder obtained in the above steps and sintering them in turn to obtain a sintered NdFeB magnet substrate blank;

[0028] D) R2 a N b The alloy powder is mixed with an organic solvent to obtain a suspension;

[0029] E) coating the suspension obtained in the above step on the surface of the NdFeB substrate blank to obtain a semi-finished product;

[0030] F) heat treating the semi-finished product obtained in the above steps to obtain a RTB sintered NdFeB magnet.

[0031] Preferably, the temperature of the quick-setting thin sheet treatment is 1400-1500°C;

[0032] The thickness of the NdFeB quick-setting sheet is 0.10-0.60 mm;

[0033] During the hydrogen crushing process, the hydrogen absorption time is 1 to 3 hours and the hydrogen absorption temperature is 20 to 300°C;

[0034] In the hydrogen crushing process, the dehydrogenation time is 3 to 7 hours and the dehydrogenation temperature is 550 to 600°C.

[0035] Preferably, during the jet milling process, a lubricant is added for grinding;

[0036] The lubricant is 0.02-0.1% of the mass of the mixed fine powder obtained by hydrogen crushing;

[0037] The average particle size of the powder after jet milling is 2 to 5 μm;

[0038] The orientation molding comprises the steps of orientation pressing and isostatic pressing performed sequentially;

[0039] The magnetic field intensity of the orientation molding is 1.2-3T.

[0040] Preferably, the sintering temperature is 1000-1200°C, the sintering time is 5-15h, and the vacuum degree is less than or equal to 0.02Pa;

[0041] The sintering further includes an aging treatment, and the aging treatment includes a first aging treatment and a second aging treatment;

[0042] The temperature of the first aging treatment is 800-980°C, and the time of the first aging treatment is 1-10 hours;

[0043] The temperature of the second aging treatment is 420-580° C., and the time of the second aging treatment is 1-8 hours.

[0044] Preferably, the heat treatment includes high temperature diffusion treatment and low temperature tempering treatment;

[0045] The temperature of the high temperature diffusion treatment is 700-1000° C., and the time of the high temperature diffusion treatment is 3-20 hours;

[0046] The temperature of the low temperature tempering treatment is 350-750° C., and the time of the low temperature tempering treatment is 1-8 hours.

[0047] The present invention provides a RTB sintered NdFeB magnet, comprising: a sintered NdFeB substrate and a diffusion alloy composited on the substrate; the substrate has a general formula of R1 in terms of mass content. x T 余量 M y1 A y2 B z ; wherein R1 is selected from at least two rare earth elements and must include Pr and Nd; A is selected from Cu, Ga and Al; M is selected from one or more of Ti, Zr and Nb and must include Ti; T is selected from Fe and Co; in the general formula of the substrate, 28.5wt%≤x≤32.0wt%, 0.13wt%≤y1≤0.5wt%, 0.2wt%≤y2≤1.35wt%, 0.8wt%≤z≤1.2wt%; the general formula of the diffusion alloy by mass content is R2 a N b; wherein R2 is selected from one or more heavy rare earth elements; N includes one or more of Al, Cu, Zn, Sn and Ga; in the general formula of the diffusion alloy, 80wt%≤a≤100wt%, b≤20wt%; the diffusion alloy accounts for 0.2wt% to 1.5wt% of the total amount of the RTB sintered NdFeB magnet; the composition of the RTB sintered NdFeB magnet has the following mass content relationship: 3(y1+y2)-[R2 a N b ]>0.5wt%. Compared with the prior art, the present invention uses Cu, Ga, Al, Ti, Zr, Nb and Fe and rare earth elements for reasonable design. At the same time, during the sintering and aging process, the composite phase is formed to improve the wettability of the grain boundary, which is conducive to the heavy rare earth elements entering the deep part of the magnet along the grain boundary during the subsequent diffusion process. In addition, by forming a specific component ratio with the diffusion source, the effect of the diffusion of the heavy rare earth elements along the grain boundary is improved, and the magnetic properties can be further improved. The present invention also specifically adds Ti / Zr / Nb elements to the alloy elements and increases the amount of addition. By controlling the fixed ratio of Ti and Cu elements, the grain refining effect of the TiCu composite phase can be utilized. Because the Ti / Zr elements cooperate with the Cu element to form Cu-Ti and Zr-Cu alloy phases, the copper-titanium phase enriched in the grain boundary of the magnetic phase becomes the pinning field center that "pins" the movement of the domain wall when the magnet is demagnetized, hindering the movement of the magnetic domain wall, thereby improving the intrinsic coercive force of the magnet alloy; at the same time, the copper-titanium phase has a "pinning" effect on the grain boundary movement of the magnetic phase grains, thereby improving the sintering temperature resistance, and no abnormal grain growth occurs. It can also very effectively prevent the change of the magnetic phase, refine the grains, and further improve the remanence, coercive force and magnetic energy product of the magnet alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a SEM electron microscope image of the sintered NdFeB magnet prepared in Example 1 of the present invention;

[0049] Figure 2 This is a SEM electron microscope image of the sintered NdFeB magnet prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0050] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.

[0051] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0052] There is no particular restriction on the purity of all raw materials in the present invention. The present invention preferably uses industrial pure materials or materials of conventional purity used in the field of sintered NdFeB magnet preparation.

[0053] The present invention provides a RTB sintered NdFeB magnet, comprising: a sintered NdFeB substrate and a diffusion alloy composited on the substrate;

[0054] The general formula of the substrate by mass content is R1 x T 余量 M y1 A y2 B z ; Wherein, R1 is selected from at least two rare earth elements and must include Pr and Nd; A is selected from Cu, Ga and Al; M is selected from one or more of Ti, Zr and Nb, and must include Ti; T is selected from Fe and Co;

[0055] In the general formula of the substrate, 28.5wt%≤x≤32.0wt%, 0.13wt%≤y1≤0.5wt%, 0.2wt%≤y2≤1.35wt%, 0.8wt%≤z≤1.2wt%;

[0056] The general formula of the diffusion alloy by mass content is R2 a N b ; Wherein, R2 is selected from one or more heavy rare earth elements; N includes one or more of Al, Cu, Zn, Sn and Ga;

[0057] In the general formula of the diffusion alloy, 80wt%≤a≤100wt%, b≤20wt%;

[0058] The diffusion alloy accounts for 0.2wt% to 1.5wt% of the total amount of the RTB sintered NdFeB magnet;

[0059] The components of the RTB sintered NdFeB magnet have the following mass content relationship:

[0060] 3(y1+y2)-[R2 a N b ]>0.5wt%.

[0061] In the present invention, in the general formula of the substrate, 28.5wt%≤x≤32.0wt%, 0.13wt%≤y1≤0.5wt%, 0.2wt%≤y2≤1.35wt%, 0.8wt%≤z≤1.2wt%, can be 29wt%≤x≤31.5wt%, 0.2wt%≤y1≤0.45wt%, 0.4wt%≤y2≤1.0wt%, 0.85wt%≤z≤1.15wt%, can be 29.5wt%≤x≤30.5wt%, 0.25wt%≤y1≤0.4wt%, 0.6wt%≤y2≤0.8wt%, 0.9wt%≤z≤1.1wt%.

[0062] In the present invention, in the general formula of the diffusion alloy, 80wt%≤a≤100wt%, b≤20wt%, may be 83wt%≤a≤97wt%, 2wt%≤b≤17wt%, may be 85wt%≤a≤95wt%, 5wt%≤b≤15wt%, may be 87wt%≤a≤93wt%, 8wt%≤b≤13wt%.

[0063] In the present invention, among the M, preferably 0.3wt%>Ti+Zr / 2+Nb / 3≥0.13wt%, Ti>0, Zr≥0, Nb≥0, more preferably 0.27wt%≥Ti+Zr / 2+Nb / 3≥0.16wt%, Ti>0, Zr≥0, Nb≥0, more preferably 0.24wt%≥Ti+Zr / 2+Nb / 3≥0.2wt%, Ti>0, Zr≥0, Nb≥0.

[0064] In the present invention, among the A, preferably 0.8wt%>Cu>0.18wt%, the Ga content is preferably 0.25wt%~0.45wt%, the Al content is preferably 0.02~0.5wt%, more preferably 0.7wt%≥Cu≥0.3wt%, the Ga content is more preferably 0.29wt%~0.4wt%, the Al content is preferably 0.1~0.4wt%, more preferably 0.6wt%≥Cu≥0.4wt%, the Ga content is more preferably 0.33wt%~0.36wt%, and the Al content is preferably 0.2~0.3wt%.

[0065] In the present invention, in the RTB sintered NdFeB magnet, the Ti-based precipitated phase is preferably a Ti-Cu phase.

[0066] In the present invention, in the RTB sintered NdFeB magnet, the mass content ratio of Ti to Cu is preferably (1-3):5, more preferably (1.4-2.6):5, and more preferably (1.8-2.2):5.

[0067] In the present invention, the substrate preferably accounts for 98.8wt% to 99.7wt% of the total amount of the RTB sintered NdFeB magnet, more preferably 99wt% to 99.5wt%, and more preferably 99.2wt% to 99.3wt%.

[0068] In the present invention, the diffusion alloy preferably accounts for 0.3wt% to 1.2wt% of the total amount of the RTB sintered NdFeB magnet, more preferably 0.5wt% to 1.0wt%, and more preferably 0.7wt% to 0.9wt%.

[0069] In the present invention, in the T, the content of Co is preferably 0.01wt% to 1.0wt%, and the balance is Fe, more preferably 0.2wt% to 0.8wt%, and more preferably 0.4wt% to 0.6wt%.

[0070] In the present invention, the heavy rare earth element preferably includes one or more of Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu and Y, and more preferably Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu or Y.

[0071] In the present invention, the average grain size of the RTB sintered NdFeB magnet after sintering is preferably 2.5-6 μm, more preferably 3-5.5 μm, more preferably 3.5-5 μm, and more preferably 4-4.5 μm.

[0072] The present invention provides a method for preparing an RTB sintered NdFeB magnet as described in any one of the above technical solutions, comprising the following steps:

[0073] A) after the raw materials are mixed according to the proportion, they are subjected to quick-setting thin sheet treatment to obtain NdFeB quick-setting thin sheets;

[0074] B) subjecting the NdFeB quick-solidification flakes obtained in the above steps to hydrogen crushing and jet milling in sequence to obtain NdFeB powder;

[0075] C) orienting and molding the NdFeB powder obtained in the above steps and sintering them in turn to obtain a sintered NdFeB magnet substrate blank;

[0076] D) R2 a N b The alloy powder is mixed with an organic solvent to obtain a suspension;

[0077] E) coating the suspension obtained in the above step on the surface of the NdFeB substrate blank to obtain a semi-finished product;

[0078] F) heat treating the semi-finished product obtained in the above steps to obtain a RTB sintered NdFeB magnet.

[0079] The invention firstly mixes raw materials according to a proportion, and then performs a quick-setting thin sheet treatment to obtain a NdFeB quick-setting thin sheet.

[0080] In the present invention, the temperature of the rapid-setting thin-sheet treatment is preferably 1400-1500°C, more preferably 1420-1480°C, and more preferably 1440-1460°C.

[0081] In the present invention, the thickness of the NdFeB quick-setting sheet is preferably 0.10-0.60 mm, more preferably 0.20-0.50 mm, and more preferably 0.30-0.40 mm.

[0082] The invention then sequentially performs hydrogen crushing and air flow milling on the NdFeB quick-solidification flakes obtained in the above steps to obtain NdFeB powder.

[0083] In the present invention, during the hydrogen crushing process, the hydrogen absorption time is preferably 1 to 3 hours, the hydrogen absorption temperature is preferably 20 to 300°C, the hydrogen absorption time is more preferably 1.4 to 2.6 hours, the hydrogen absorption temperature is more preferably 70 to 250°C, the hydrogen absorption time is more preferably 1.8 to 2.2 hours, and the hydrogen absorption temperature is more preferably 120 to 200°C.

[0084] In the present invention, during the hydrogen crushing process, the dehydrogenation time is preferably 3 to 7 hours, the dehydrogenation temperature is preferably 550 to 600°C, the dehydrogenation time is preferably 3.5 to 6.5 hours, the dehydrogenation temperature is preferably 560 to 590°C, the dehydrogenation time is preferably 4 to 6 hours, and the dehydrogenation temperature is preferably 570 to 580°C.

[0085] In the present invention, during the jet milling process, a lubricant is preferably added for grinding.

[0086] In the present invention, the lubricant is preferably 0.02-0.1% by mass of the mixed fine powder obtained by hydrogen crushing, more preferably 0.03-0.09%, more preferably 0.04-0.08%, more preferably 0.05-0.07% by mass.

[0087] In the present invention, the average particle size of the powder after jet milling is preferably 2 to 5 μm, more preferably 2.5 to 4.5 μm, and more preferably 3 to 4 μm.

[0088] The present invention then sequentially performs orientation molding and sintering on the NdFeB powder obtained in the above steps to obtain a sintered NdFeB magnet substrate blank.

[0089] In the present invention, the orientation molding preferably includes the steps of orientation pressing and isostatic pressing performed sequentially.

[0090] In the present invention, the magnetic field intensity of the orientation molding is preferably 1.2-3T, more preferably 1.6-2.6T, and more preferably 2.0-2.2T.

[0091] In the present invention, the sintering temperature is preferably 1000-1200°C, the sintering time is preferably 5-15h, and the vacuum degree is preferably less than or equal to 0.02Pa. The sintering temperature is preferably 1040-1160°C, the sintering time is preferably 7-13h, and the vacuum degree is preferably less than or equal to 0.015Pa. The sintering temperature is preferably 1080-1120°C, the sintering time is preferably 9-11h, and the vacuum degree is preferably less than or equal to 0.01Pa.

[0092] In the present invention, the sintering preferably further includes an aging treatment, and the aging treatment preferably includes a first aging treatment and a second aging treatment.

[0093] In the present invention, the temperature of the first aging treatment is preferably 800-980° C., more preferably 830-950° C., more preferably 860-920° C. The time of the first aging treatment is preferably 1-10 hours, more preferably 3-8 hours, more preferably 5-6 hours.

[0094] In the present invention, the temperature of the second aging treatment is preferably 420-580°C, more preferably 450-550°C, more preferably 480-520°C, and the time of the second aging treatment is preferably 1-8 hours, more preferably 2.5-6.5 hours, more preferably 4-5 hours.

[0095] The present invention then converts R2 a N b The alloy powder is mixed with an organic solvent to obtain a suspension.

[0096] The present invention further coats the suspension obtained in the above steps on the surface of the NdFeB substrate blank to obtain a semi-finished product.

[0097] In the present invention, the semi-finished product obtained in the above steps is finally heat treated to obtain an RTB sintered NdFeB magnet.

[0098] In the present invention, the heat treatment preferably includes a high-temperature diffusion treatment and a low-temperature tempering treatment.

[0099] In the present invention, the temperature of the high temperature diffusion treatment is preferably 700-1000°C, more preferably 750-950°C, more preferably 800-900°C, and the time of the high temperature diffusion treatment is preferably 3-20 hours, more preferably 7-16 hours, more preferably 11-12 hours.

[0100] In the present invention, the temperature of the low-temperature tempering treatment is preferably 350-750°C, more preferably 400-700°C, more preferably 450-650°C, more preferably 500-600°C, and the time of the low-temperature tempering treatment is preferably 1-8 hours, more preferably 2.5-6.5 hours, more preferably 4-5 hours.

[0101] The present invention is to complete and refine the overall technical solution, and better improve the comprehensive performance of the RTB sintered NdFeB magnet. The above-mentioned RTB sintered NdFeB magnet and its preparation method may specifically include the following contents:

[0102] A RTB sintered NdFeB magnet comprises a sintered NdFeB substrate and a diffusion alloy composited on the substrate, wherein the substrate is R1 x T 余量 M y1 A y2 B z ; Diffusion alloy is R2 a N b ;

[0103] In the substrate, x, y1, y2, and z are the mass percentages of the corresponding elements, respectively, 28.5wt%≤x≤32.0wt%, 0.13wt%≤y1≤0.5wt%, 0.2wt%≤y2≤1.35wt%, 0.8wt%≤z≤1.2wt%; the diffusion alloy accounts for 0.2-1.5wt% of the total amount of the magnet, among which 80wt%≤a≤98wt%, 2wt%≤b≤20wt%.

[0104] The R1 is selected from one or more rare earth elements and must contain Pr and Nd;

[0105] A is selected from Cu, Ga and Al;

[0106] M is selected from one or more of Ti, Zr and Nb, and must contain Ti;

[0107] T is selected from Fe and Co;

[0108] R2 is selected from one or more heavy rare earth elements;

[0109] N includes one or more of Al, Cu, Zn, Sn and Ga;

[0110] The addition amount of the sintered NdFeB magnet components has the following relationship:

[0111] 3(y1+y2)-[R2 a N b ]>0.5wt%.

[0112] Specifically, in the M, 0.3wt%>Ti+Zr / 2+Nb / 3≥0.13wt%, Ti>0, Zr≥0, Nb≥0; in the A, 0.8wt%>Cu>0.18wt%, the Ga content is 0.25-0.45wt%, and the Al content is 0.02-0.5wt%; wherein the Ti-based precipitated phase is a Ti-Cu phase, and the mass percentage ratio of Ti to Cu is 1:5-3:5.

[0113] Specifically, the substrate accounts for 98.8-99.7wt% of the total amount of the magnet, and the diffusion alloy accounts for 0.3-1.2wt% of the total amount of the magnet.

[0114] Specifically, the content of Co in the T is 0-1.0wt%, and the balance is Fe.

[0115] Specifically, the average grain size of the magnet after sintering is 2.5 to 6 μm.

[0116] The present invention also provides a method for preparing a sintered NdFeB magnet according to any one of the above technical solutions, comprising the following steps:

[0117] A) the raw materials are mixed according to the proportion and then subjected to quick-setting thin sheet treatment to obtain NdFeB quick-setting thin sheets;

[0118] B) subjecting the NdFeB quick-solidified flakes to hydrogen crushing and jet milling in sequence to obtain NdFeB powder;

[0119] C) orienting and molding the NdFeB powder and sintering the powder in sequence to obtain a sintered NdFeB magnet substrate blank;

[0120] D) R2 a N b The alloy powder is mixed with an organic solvent to obtain a suspension;

[0121] E) coating the suspension obtained in the above step on the surface of the NdFeB substrate blank to obtain a semi-finished product;

[0122] F) after the semi-finished product obtained by the above steps is subjected to heat treatment, a neodymium iron boron magnet is obtained.

[0123] Specifically, the temperature of the quick-setting thin sheet treatment is 1400-1500° C., and the thickness of the NdFeB quick-setting thin sheet is 0.10-0.60 mm.

[0124] Specifically, in the hydrogen crushing process, the hydrogen absorption time is 1 to 3 hours, the hydrogen absorption temperature is 20 to 300°C, the dehydrogenation time is 3 to 7 hours, and the dehydrogenation temperature is 550 to 600°C.

[0125] Specifically, during the jet milling process, a lubricant is added for grinding, and the lubricant is 0.02-0.1% of the mass of the mixed fine powder obtained by hydrogen crushing. The average particle size of the powder after the jet milling is 2-5 μm.

[0126] Specifically, the orientation molding includes orientation pressing and isostatic pressing performed in sequence; the magnetic field intensity of the orientation molding is 1.2-3T.

[0127] Specifically, the sintering temperature in step C) is 1000-1200° C., the sintering time is 5-15 hours, and the vacuum degree is less than or equal to 0.02 Pa.

[0128] The sintering further includes an aging treatment, and the aging treatment includes a first aging treatment and a second aging treatment;

[0129] The temperature of the first aging treatment is 800-980°C, and the time of the first aging treatment is 1-10 hours;

[0130] The temperature of the second aging treatment is 420-580° C., and the time of the second aging treatment is 1-8 hours.

[0131] Specifically, the heat treatment in step F) includes high temperature diffusion treatment and low temperature tempering treatment; the temperature of the high temperature diffusion treatment is 700-1000° C., and the time of the high temperature diffusion treatment is 3-20 hours.

[0132] The temperature of the low temperature tempering treatment is 350-750° C., and the time of the low temperature tempering treatment is 1-8 hours.

[0133] The above content of the present invention provides a RTB sintered NdFeB magnet and a preparation method thereof. The present invention uses Cu, Ga, Al, Ti, Zr, Nb and Fe and rare earth elements for reasonable design. At the same time, during the sintering and aging process, the formation of a composite phase can also improve the wettability of the grain boundary, which is conducive to the heavy rare earth elements entering the deep part of the magnet along the grain boundary during the subsequent diffusion process, and by forming a specific component ratio with the diffusion source, the effect of the diffusion of the heavy rare earth elements along the grain boundary is improved, which can further improve the magnetic properties. The present invention also specifically adds Ti / Zr / Nb elements to many alloy elements and increases their addition amount. By controlling the fixed ratio of Ti and Cu elements, the grain refining effect of the TiCu composite phase can be utilized. Because the Ti / Zr elements cooperate with the Cu element to form Cu-Ti and Zr-Cu alloy phases, the copper-titanium phase enriched in the grain boundary of the magnetic phase becomes the pinning field center that "pins" the movement of the domain wall when the magnet is demagnetized, hindering the movement of the magnetic domain wall, thereby improving the intrinsic coercive force of the magnet alloy; at the same time, the copper-titanium phase has a "pinning" effect on the grain boundary movement of the magnetic phase grains, thereby improving the sintering temperature resistance, and no abnormal grain growth occurs. It can also very effectively prevent the change of the magnetic phase, refine the grains, and further improve the remanence, coercive force and magnetic energy product of the magnet alloy.

[0134] In order to further illustrate the present invention, a RTB sintered NdFeB magnet and a preparation method thereof provided by the present invention are described in detail below in combination with examples. However, it should be understood that these examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention, and the protection scope of the present invention is not limited to the following examples.

[0135] Example parameters

[0136] The base material is R1 x T 余量 M y1 A y2 B z ; Diffusion alloy is R2 a N b (A is selected from Cu, Ga and Al;)

[0137] Satisfies: Formula 1: 3(y1+y2)-[R2 a N b ]>0.5wt%;

[0138] Formula 2: 0.3wt%>Ti+Zr / 2+Nb / 3≥0.13wt%;

[0139] Formula 3: The mass percentage ratio of Ti and Cu is 1:5 to 3:5.

[0140] See Table 1, which is a raw material formula data table (wt %) of the examples and comparative examples of the present invention.

[0141] Table 1

[0142]

[0143]

[0144] Example 1

[0145] The ingredients were prepared according to Example 1 shown in Table 1, the raw materials obtained were smelted in a vacuum induction melting furnace, the molten liquid obtained was cast at 1450°C, and cooled on a copper roller at a rotation speed of 42 rpm to obtain a NdFeB alloy casting with an average thickness of 0.35 mm; the casting was hydrogen crushed, the hydrogen absorption time in the hydrogen crushing process was 1.5 hours, the dehydrogenation time was 5.5 hours, the dehydrogenation temperature was 580°C, and it was cooled for 2 hours, the obtained powder was jet milled to obtain a powder with a particle size D50 of 4.2 μm, the obtained powder was subjected to magnetic field orientation molding treatment at a magnetic field strength of 1.6 T in a sealed oxygen-free glove box, and then isostatic pressing treatment was performed at 200 MPa to obtain a magnet blank; the magnet blank was sintered at 1060°C for 8 hours, then aged at 890°C for 3 hours, and finally aged at 520°C for 5 hours to obtain a NdFeB magnet substrate. The 0.6wt% Tb powder in the magnet was mixed with an organic solvent, coated on the surface of the NdFeB substrate, and then placed in a vacuum furnace for diffusion treatment at 900℃*8h, followed by tempering treatment at 600℃*5h to obtain a sintered NdFeB magnet. The performance results are shown in Table 2.

[0146] Comparative Example 1

[0147] The ingredients were prepared according to Comparative Example 1 shown in Table 1, and the preparation process was the same as that of Example 1 to obtain a NdFeB substrate and a magnet. The properties are shown in Table 2.

[0148] Table 2 Performance data of magnets prepared in Example 1 and Comparative Example 1

[0149]

[0150] analyze:

[0151] In Example 1, Formula 1=2.1; Formula 2=0.2; Formula 3=0.5, which are within the range of the formulas.

[0152] For comparative example 1, formula 1=1.5; formula 2=0.05; and formula 3=0, which is not within the range of formula 2.

[0153] It can be seen from the performance that the coercive force of Example 1 is increased by 2K compared with that of Comparative Example 1.

[0154] See also Figure 1 , Figure 1 The SEM electron microscope images of the sintered NdFeB magnet prepared in Example 1 of the present invention are shown in FIG. The upper image is an electron microscope image at 500 times magnification, and the lower image is an electron microscope image at 1000 times magnification.

[0155] See also Figure 2 , Figure 2 The SEM electron microscope images of the sintered NdFeB magnet prepared in Comparative Example 1 of the present invention are shown in FIG. The upper image is an electron microscope image at 500 times magnification, and the lower image is an electron microscope image at 1000 times magnification.

[0156] It can be seen from the SEM image that under the condition of using the same particle size D50: 4.2 microns in powder making, the grains of the essential element Ti added in the present invention are finer and evenly distributed, achieving the purpose of grain refinement.

[0157] Example 2

[0158] The ingredients were prepared according to Example 2 shown in Table 1, the raw materials obtained were smelted in a vacuum induction melting furnace, the molten liquid obtained was cast at 1450°C, and cooled on a copper roller at a rotation speed of 42 rpm to obtain a NdFeB alloy casting with an average thickness of 0.35 mm; the casting was hydrogen crushed, the hydrogen absorption time in the hydrogen crushing process was 1.5 hours, the dehydrogenation time was 5.5 hours, the dehydrogenation temperature was 600°C, and it was cooled for 2 hours, the obtained powder was jet milled to obtain a powder with a particle size D50 of 4.2 μm, the obtained powder was subjected to magnetic field orientation molding treatment at a magnetic field strength of 1.6 T in a sealed oxygen-free glove box, and then isostatic pressing treatment was performed at 200 MPa to obtain a magnet blank; the magnet blank was sintered at 1070°C for 8 hours, then aged at 890°C for 3 hours, and finally aged at 520°C for 5 hours to obtain a NdFeB magnet substrate. The 0.5wt% Tb powder in the magnet was mixed with an organic solvent, coated on the surface of the NdFeB substrate, and then placed in a vacuum furnace for diffusion treatment at 890℃*8h, followed by tempering treatment at 610℃*5h to obtain a sintered NdFeB magnet. The performance results are shown in Table 3.

[0159] Comparative Example 2

[0160] The ingredients were prepared according to Comparative Example 2 shown in Table 1, and the preparation process was the same as that of Example 2 to obtain a NdFeB substrate and a magnet. The properties are shown in Table 3.

[0161] Table 3 Performance data of magnets prepared in Example 2 and Comparative Example 2

[0162]

[0163] analyze:

[0164] In Example 2, Formula 1 = 2.8; Formula 2 = 0.25; Formula 3 = 0.5. These are within the range of the formula.

[0165] For comparative example 2, formula 1=4.3; formula 2=0.25; and formula 3=0.1875, which is not within the range of formula 3.

[0166] It can be seen from the performance that the coercive force of Example 2 is increased by 0.9K compared with that of Comparative Example 2.

[0167] Example 3

[0168] The ingredients were prepared according to Example 3 shown in Table 1, the raw materials obtained were smelted in a vacuum induction melting furnace, the molten liquid obtained was cast at 1480°C, and cooled on a copper roller at a rotation speed of 40 rpm to obtain a NdFeB alloy casting sheet with an average thickness of 0.30 mm; the casting sheet was hydrogen crushed, the hydrogen absorption time in the hydrogen crushing process was 1 hour, the dehydrogenation time was 5 hours, the dehydrogenation temperature was 600°C, and it was cooled for 2 hours, the obtained powder was jet milled to obtain a powder with a particle size D50 of 4.2 μm, the obtained powder was subjected to magnetic field orientation molding treatment in a sealed oxygen-free glove box under a 17320 Gauss magnetic field, and then isostatic pressing treatment was performed at 200 MPa to obtain a magnet blank; the magnet blank was sintered at 1060°C for 6 hours, then aged at 920°C for 2 hours, and finally aged at 525°C for 5 hours to obtain a NdFeB magnet substrate. The 0.5wt% Tb powder in the magnet was mixed with an organic solvent, coated on the surface of the NdFeB substrate, and then placed in a vacuum furnace for diffusion treatment at 880℃*8h, followed by tempering treatment at 700℃*5h to obtain a sintered NdFeB magnet. The performance results are shown in Table 4.

[0169] Comparative Example 3

[0170] The ingredients were prepared according to Comparative Example 3 shown in Table 1, and the preparation process was the same as that of Example 3 to obtain a NdFeB substrate and a magnet. The properties are shown in Table 4.

[0171] Table 4 Performance data of magnets prepared in Example 3 and Comparative Example 3

[0172]

[0173] analyze:

[0174] In Example 3, Formula 1 = 1.15; Formula 2 = 0.15; Formula 3 = 0.5. These are within the range of the formula.

[0175] Comparative Example 3 is Formula 1=0.4; Formula 2=0.15; Formula 3=1, which is not within the range of Formulas 1 and 3.

[0176] It can be seen from the performance that the coercive force of Example 3 is increased by 1.5K compared with that of Comparative Example 3.

[0177] The above is a detailed introduction to a RTB sintered NdFeB magnet and a preparation method thereof provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method and its core ideas of the present invention, including the best mode, and also enables any technician in the field to practice the present invention, including manufacturing and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the text of the claims, or if they include equivalent structural elements that are not substantially different from the text of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A RTB sintered NdFeB magnet, characterized in that: include: Sintered NdFeB substrate and diffusion alloy composited on the substrate; The general formula of the substrate by mass content is R1 x T 余量 M y1 A y2 B z ; Wherein, R1 is selected from at least two rare earth elements and must include Pr and Nd; A is selected from Cu, Ga and Al; M is selected from one or more of Ti, Zr and Nb, and must include Ti; T is selected from Fe and Co; In the general formula of the substrate, 28.5wt%≤x≤32.0wt%, 0.13wt%≤y1≤0.5wt%, 0.2wt%≤y2≤1.35wt%, 0.8wt%≤z≤1.2wt%; The general formula of the diffusion alloy by mass content is R2 a N b ; Wherein, R2 is selected from one or more heavy rare earth elements; N includes one or more of Al, Cu, Zn, Sn and Ga; In the general formula of the diffusion alloy, 80wt%≤a≤100wt%, b≤20wt%; The diffusion alloy accounts for 0.2wt% to 1.5wt% of the total amount of the RTB sintered NdFeB magnet; The components of the RTB sintered NdFeB magnet have the following mass content relationship: <h2 style=";text-align:left;direction:ltr">3(y1+y2)-[R2<h2 style=";text-align:left;direction:ltr"> a <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> b <h2 style=";text-align:left;direction:ltr"> ]<0.5wt%。 2. The RTB sintered NdFeB magnet according to claim 1, characterized in that: In the M, 0.3wt%>Ti+Zr / 2+Nb / 3≥0.13wt%, Ti>0, Zr≥0, Nb≥0; In the A, 0.8wt%>Cu>0.18wt%, the content of Ga is 0.25wt%-0.45wt%, and the content of Al is 0.02-0.5wt%.

3. The RTB sintered NdFeB magnet according to claim 1, characterized in that: In the RTB sintered NdFeB magnet, the Ti-based precipitated phase is a Ti-Cu phase; In the RTB sintered NdFeB magnet, the mass content ratio of Ti to Cu is (1-3):

5.

4. The RTB sintered NdFeB magnet according to claim 1, characterized in that: The substrate accounts for 98.8wt% to 99.7wt% of the total amount of the RTB sintered NdFeB magnet; The diffusion alloy accounts for 0.3wt% to 1.2wt% of the total amount of the RTB sintered NdFeB magnet.

5. The RTB sintered NdFeB magnet according to claim 1, characterized in that: In the T, the content of Co is 0.01wt% to 1.0wt%, and the balance is Fe; The heavy rare earth element includes one or more of Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu and Y; The RTB sintered NdFeB magnet has an average grain size of 2.5 to 6 μm after sintering.

6. A method for preparing a RTB sintered NdFeB magnet according to any one of claims 1 to 5, characterized in that: The following steps are involved: A) the raw materials are mixed according to the proportion and then subjected to quick-setting thin sheet treatment to obtain NdFeB quick-setting thin sheets; B) subjecting the NdFeB quick-solidification flakes obtained in the above steps to hydrogen crushing and jet milling in sequence to obtain NdFeB powder; C) orienting and molding the NdFeB powder obtained in the above steps and sintering them in turn to obtain a sintered NdFeB magnet substrate blank; D) R2 a N b The alloy powder is mixed with an organic solvent to obtain a suspension; E) coating the suspension obtained in the above step on the surface of the NdFeB substrate blank to obtain a semi-finished product; F) heat treating the semi-finished product obtained in the above steps to obtain a RTB sintered NdFeB magnet.

7. The preparation method according to claim 6, characterized in that: The temperature of the quick-setting thin slice treatment is 1400-1500°C; The thickness of the NdFeB quick-setting sheet is 0.10-0.60 mm; During the hydrogen crushing process, the hydrogen absorption time is 1 to 3 hours and the hydrogen absorption temperature is 20 to 300°C; In the hydrogen crushing process, the dehydrogenation time is 3 to 7 hours and the dehydrogenation temperature is 550 to 600°C.

8. The preparation method according to claim 6, characterized in that: During the jet milling process, a lubricant is added to grind the powder; The lubricant is 0.02-0.1% of the mass of the mixed fine powder obtained by hydrogen crushing; The average particle size of the powder after jet milling is 2 to 5 μm; The orientation molding comprises the steps of orientation pressing and isostatic pressing performed sequentially; The magnetic field intensity of the orientation molding is 1.2-3T.

9. The preparation method according to claim 6, characterized in that: The sintering temperature is 1000-1200° C., the sintering time is 5-15 hours, and the vacuum degree is less than or equal to 0.02 Pa; The sintering further includes an aging treatment, and the aging treatment includes a first aging treatment and a second aging treatment; The temperature of the first aging treatment is 800-980°C, and the time of the first aging treatment is 1-10 hours; The temperature of the second aging treatment is 420-580° C., and the time of the second aging treatment is 1-8 hours.

10. The preparation method according to claim 6, characterized in that: The heat treatment includes high temperature diffusion treatment and low temperature tempering treatment; The temperature of the high temperature diffusion treatment is 700-1000° C., and the time of the high temperature diffusion treatment is 3-20 hours; The temperature of the low temperature tempering treatment is 350-750° C., and the time of the low temperature tempering treatment is 1-8 hours.